Characterization of MoN coatings for pistons in a diesel engine - Hazar, Hanbey (Elsevier Sci Ltd, 2010)
In this study, the surface of a piston in a diesel engine was coated with molybdenum nitride (MoN) by using the arc PVD method, and its surface behaviour was subsequently analyzed. Analyses of microhardness, SEM, X-ray and surface roughness were carried out in order to examine surface characteristics of pistons. It is found that the hardness of coated piston is 2000 +/- 400 HV while hardness uncoated piston 123 HV. The results show less deformation and fewer scratches due to wear on the MoN-coated piston as compared to uncoated one. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Wear